How and why did Rudolf Carnap overcome metaphysics? - Kozachenko Надія (Actual Problems of Mind, 2023)
The article gives a brief outline of the genesis of Rudolph Carnap’s fundamental article “The Overcoming of Metaphysics by the Logical Analysis of Language“. We consider the scientific path of Rudolph Carnap which, together with the orientation of the Vienna Circle, leads to an anti-metaphysical attitude embodied in the “Logical Construction of the World“ and the “Scientific Understanding of the World“. We highlight the cultural and historical conditions for the emergence of “Overcoming Metaphysics through the Logical Analysis of Language“, its scientific and philosophical foundations, and analyse the influence of contemporaries on the development of Carnap’s relevant ideas. We then carry out a detailed analysis of Carnap’s method of overcoming metaphysics. We have attempted to reconstruct the movement of Carnapian ideas in a broad philosophical context, drawing on his earlier works and the explorations of the philosophers on whom he relied. We trace not only the philosophical but also the cultural component of Carnap’s attempt to reject Heidegger’s metaphysics. We extend the context of opposition to traditional metaphysics and attempts to rethink it, beginning with Kant, who was the last significant common figure of analytic and continental philosophy, and at the same time a harbinger of the divergence of their paths. We argue that the philosophers whose work we now regard as the origins of the separation of the analytic and continental traditions, including Heidegger and Carnap, shared a common philosophical background shaped by the intellectual space of post-World War I Germany, which was particularly filled with the neoKantianism of the Baden School, Husserlian phenomenology, and the life philosophy of Dilthey and Nietzsche. All these trends criticised traditional metaphysics and contributed to the renewal of philosophical methods. Carnap’s approach to overcoming metaphysics expressed the orientation of a whole galaxy of philosophers whose aim was to create a new way of doing scientific philosophy. Despite further debate and even criticism of Carnap by his followers, the influence of his methodological guidelines on the rethinking of metaphysics cannot be denied. Modern analytical metaphysics is a full-fledged methodological adherent of Carnapian methods - definiteness, reductiveness, explication, the purpose of which is the construction of categorical systems that allow the best description of reality from the position appropriate to a given study.